2005
DOI: 10.1080/09588220500442772
|View full text |Cite
|
Sign up to set email alerts
|

Task design for audiographic conferencing: Promoting beginner oral interaction in distance language learning

Abstract: ABSTRACT:This paper presents the challenges involved in designing a full set of online tutorial materials for a beginners' Spanish course for distance language learners utilising an online audiographic conferencing VLE for synchronous oral interaction. Although much has been written about task design and taskbased learning and teaching (TBLT) in language learning (Johnson, 2003;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 17 publications
1
38
0
1
Order By: Relevance
“…This confirms observations of other researchers (e.g. Rosell-Aguilar, 2005) that careful task design is important for the success of communicative language tutorials.…”
Section: Resultssupporting
confidence: 91%
“…This confirms observations of other researchers (e.g. Rosell-Aguilar, 2005) that careful task design is important for the success of communicative language tutorials.…”
Section: Resultssupporting
confidence: 91%
“…Some issues, like the lack of appropriate learning attitudes and strategies and the challenge of engaging students in active participation, are phenomena that have also been observed in face‐to‐face TBLT classrooms (Carless, 2002; Littlewood, 2007; McDonough & Chaikitmongkol, 2007). Some issues, like the use of the target language and the tension between teacher control and the need to facilitate student‐centered learning, are similar challenges to those that confront face‐to‐face TBLT classrooms, but are exacerbated by the lack of paralinguistic cues, the anonymity and the enhanced ambiguity in the online context (Rosell‐Aguilar, 2005). Other issues, like the time pressure in completing the pre–during–post TBLT cycle and the difficulty in building up and fostering rapport with students and among students, are quite unique to the online context (Hampel, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The above two studies examined learners with an intermediate level of language proficiency and above, which makes one wonder whether the same paradigm could be used on beginner learners, ab initio learners in particular. Although Duran and Ramaut (2006) and Rosell-Aguilar (2005) explored the issues related to the design of tasks for online beginner learners, little data is available on the actual implementation of TBLT in such classrooms.…”
Section: Tblt In Online Classroomsmentioning
confidence: 99%
“…Effective aural tasks should offer comprehensible input and generate opportunities to produce modified output. In -411-addition, Rosell-Aguilar (2005) suggested that effective mobile tasks have the following main features: (1) they are relevant to students" goals, (2) promote real and meaningful communicative practice, (3) offer corrective feedback, scaffolding instructor mediation, and opportunities for questions, (4) are organized around a communicative goal, (5) present contextually contingent lexico-grammar, and (6) use authentic materials. The above recommendations have to be regarded alongside with mobile learning object design principles recommended by literature.…”
Section: Mall Design Principlesmentioning
confidence: 99%